The brand of Professional football club and the method for promotion An analytical study of the brand licensing method of the professional football club - Hamadi, Djamel; Gattaf, Mohamed; Goual, Mostafa (Journal of Excellence for Economics and Management Research, 2020)
This study aims to highhight the subject of brand which considdered as the identity of sports club,and consolidate mental image of costumers.The inportance of sports promotion and services in the traget market ,though marketing strategies this seek to achieve the communication procedure and information about consumers sprots products and gools by using methods that promote the brand of professional football club awariress.